Exports, international investment, and plant performance: evidence from a non-parametric test - Sourafel Girma; Holger Görg; Eric Strobl (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper compares the performance of purely domestic plants, domestic exporters and domestic multinationals. For our empirical analysis we utilise a non-parametric approach based on the principle of first order stochastic dominance. We find that the distributions for multinationals dominate that of domestic exporters and non-exporters, while we do not find clear differences in plant performance between domestic exporters and non-exporters.
Keywords: D21; F23; F14; 330; exporting; FDI; multinationals; productivity; profitability; plant heterogeneity; Multinationales Unternehmen; Unternehmensentwicklung; Außenhandelswirtschaft; Direktinvestition; Vergleich; Produktivität; Rentabilität; Schätzung; Irland